(untitled) (Revista Apotheke, 2024)
This essay reports and analyzes the theoretical and practical actions developed in the disciplines “Pictorial Processes” and “Pictorial Representations”, offered in the bachelor’s and undergraduate courses at the State University of Santa Catarina, both taught by Artist Professor Doctor Jociele Lampert, in the second semester of 2023. Based on the understanding that the ontological tripod “doing/acting/feeling”, according to Dewey (2010), is constructed through the quality of a creative process, we propose to carry out a visual analysis of the space of artistic production the UDESC/SC Painting Studio, in different contexts, and in the dialogical relationship between teacher and student, especially in qualifying the experience in Art classes, whether through the construction of knowledge, challenges or other experiments that demand the effort to teach and learn. In this way, through a visual language of teaching and learning, the “Aula Ateliê” (Lampert, 2021) developed in this process, present a methodology based on the relationship of theory and practice that bring perspectives on the teaching of visual arts, in the conceptions of knowledge, unique, shared experiences, and in poetic reflection, contributions to the initial training of future teachers and graduates of Visual Arts.